Effects of dietary inclusion of citrus pulp and rockrose soft stems and leaves on lamb meat quality and fatty acid composition. (9th October 2017) - Francisco, A.; Alves, S. P.; Portugal, P. V.; Dentinho, M. T.; Jerónimo, E.; Sengo, S.; Almeida, J.; Bressan, M. C.; Pires, V. M. R.; Alfaia, C. M.; Prates, J. A. M.; Bessa, R. J. B.; et al.
Abstract : Meat from lambs finished with high-starch diets often contains low concentration of vaccenic ( t 11-18:1) and rumenic ( c 9, t 11-18:2) acids and high concentration of t 10-18:1. We hypothesized that replacing cereals by dehydrated citrus pulp (DCP) and the inclusion of tanniferous feed sources in oil supplemented diets might reduce the accumulation of t 10-18:1 and increase the t 11-18:1 and c 9, t11-18:2 in lamb meat, without affecting the productive performance. In total, 32 lambs were assigned to four diets which combine two factors: basal diet (BD) (cereals v. DCP) and Cistus ladanifer (CL) (0 v. 150 g/kg dry matter). Feed intake, average daily weight gain and carcass traits were not affected by treatments, except for dressing percentage that was reduced with DCP ( P =0.046). Both DCP and C. ladanifer reduced tenderness and juiciness of meat, and C. ladanifer also reduced ( P <0.001) meat overall acceptability. Intramuscular fat and the concentration of saturated and polyunsaturated fatty acids (FA) were not affected ( P >0.05) by diets. However, DCP increased the proportions of odd-chain FA ( P =0.005) and several minor biohydrogenation (BH) intermediates in meat lipids. C. ladanifer had few effects on meat FA profile. The proportions of t 11-18:1 and c 9, t 11-18:2 were high in all diets (5.4% and 1.5% of total FA, respectively) and were not influenced by the treatments. Basal diet and CL showed some significant interactions concerning FA composition of intramuscular fat. In diets without C. ladanifer, replacement of cereals by DCP increased the 18:0 ( P <0.05) and decreased t 10, c 12-18:2 ( P <0.05), t 10-18:1 ( P <0.10) and t 10-/ t 11-18:1 ratio ( P <0.10) with a large reduction of the individual variation for t 10-18:1 and of t 10-/ t 11-18:1 ratio. Combined with cereals, C. ladanifer increased 18:0 and reduced the BH intermediates in meat. Replacement of cereals by DCP seems to promote a more predictable FA profile in lamb meat, reducing the risk of t 10-shifted BH pathways in the rumen.